Digital Transformation in Indonesian Migrant Worker Registration Services at the Provincial Manpower and Transmigration Office of West Nusa Tenggara - Nurjulianti Nurjulianti; Rahmad Hidayat; Hidayatullah Hidayatullah (The Future of Education Journal, 2026)
Digital transformation represents a government effort to enhance the quality of public services through the utilization of information technology. The Manpower and Transmigration Agency of West Nusa Tenggara Province has implemented a digital-based registration service for Indonesian Migrant Workers (TKI) using the Sisnaker and SiapKerja applications. However, implementation faces various challenges, such as low public digital literacy, data verification obstacles, system technical issues, and limited supporting infrastructure. This study aims to analyze the digital transformation of TKI registration services and identify the factors influencing its implementation. A qualitative research method with a descriptive approach was employed. Data collection techniques included observation, interviews, and documentation. Research informants consisted of employees from the Manpower and Transmigration Agency of West Nusa Tenggara Province and members of the public utilizing the digital TKI registration services. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the digital transformation of TKI registration services has facilitated easier access, accelerated administrative processes, improved service efficiency, and supported transparency through the use of the Sisnaker and SiapKerja applications. Nevertheless, implementation has not been optimal due to several factors: limited human resource competence, low public digital literacy, internet network issues, application system disruptions, and budget constraints regarding digital service development. Therefore, enhancing human resource capacity, strengthening information technology infrastructure, optimizing public outreach, and securing sustainable policy and budgetary support are essential for the digital transformation of TKI registration services to function more effectively.